First report of Banana bunchy top virus on heliconia (Heliconia spp.) in Bali, Indonesia - I Made Arimbawa; Gusti Ngurah Alit Susanta Wirya; I Putu Sudiarta (Universitas Lampung, 2022)
Banana bunchy top virus (BBTV) mostly infects Musa spp. which causes banana bunchy top disease (BBTD), the most devastating viral disease in banana cultivation all over the world. During field survey in Sekar Bumi Tropical Farm located in Kerta Village, 15 heliconia plant samples showed green streak on lamina leaves that similar to common BBTD symptoms were collected. Further research was then conducted to identify molecular characteristic of BBTD in heliconia showing green streak. Molecular identification was conducted using polymerase chain reaction (PCR). Specific primers to amplified DNA target were used in this study: mRep/F (5’-GCGTGAAACGCACAAAAGGCC-3’) and mRep/R (5’-GCATACGTTGTCAAACCTTCTCCTC-3’). The expected 240 bp fragment target of partial master replication (mRep) gene was successfully amplified from ten out of 15 samples. Sequence analysis confirmed that the symptomatic heliconia samples were infected with BBTV and falls into the same clade with BBTV from the Asian Group.